Herakleides Pontikos und die ps.-plutarchische Schrift Περὶ μουσικῆς - Lucarini, Carlo M. (Hyperboreus, 2020)
The paper presents a detailed Quellenanalyse of chapters 3–10 of Ps.-Plutarch’s De musica. The aim is to refute the widespread view that these chapters derive from Heraclides of Pontus. Only the third chapter, a part of the fourth, and some small pieces of the ﬁfth and eighth chapters seem to derive from Heraclides. Elsewhere there is no indication of Heraclidean inﬂuence. It is also improbable that the anonymous compiler found the quotations from Glaucos of Rhegium in Heraclides. Chapters 8–10 (where we read the well- known account about the δευτέρα κατάστασις) are taken mainly from a source that has some connection with the musicians called ἁρμονικοί.